2009
DOI: 10.1038/ijo.2009.124
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled study of the long-term efficacy and safety of diethylpropion in the treatment of obese subjects

Abstract: Objective: To evaluate the efficacy of diethylpropion on a long-term basis, with emphasis in cardiovascular and psychiatric safety aspects. Design: Randomized, double-blind, placebo-controlled trial Measurements: Following a 2-week screening period, 69 obese healthy adults received a hypocaloric diet and were randomized to diethylpropion 50 mg BID (n ¼ 37) or placebo (n ¼ 32) for 6 months. After this period, all participants received diethylpropion in an open-label extension for an additional 6 months. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 35 publications
1
54
0
3
Order By: Relevance
“…Previous studies in humans revealed that at appropriate concentrations, DEP, PHEN, and BUP produce weight loss (Hendricks et al 2009) with the order DEP Ն PHEN Ͼ BUP (Cercato et al 2009;Suplicy et al 2014). In the present study, using rats, we found that DEP20 was slightly more potent than PHEN20 with regard to weight loss (Fig.…”
Section: Comparison Of the Appetite Suppressantssupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies in humans revealed that at appropriate concentrations, DEP, PHEN, and BUP produce weight loss (Hendricks et al 2009) with the order DEP Ն PHEN Ͼ BUP (Cercato et al 2009;Suplicy et al 2014). In the present study, using rats, we found that DEP20 was slightly more potent than PHEN20 with regard to weight loss (Fig.…”
Section: Comparison Of the Appetite Suppressantssupporting
confidence: 62%
“…For humans, after 5-6 mo of treatment their weight loss plateaus. From this point their body weight is either maintained or is slowly increased (Cercato et al 2009). Although the mechanisms explaining why appetite suppressants develop tolerance are largely unknown, we found that LFP oscillations in the NAc shell can be used as a biomarker to determine when tolerance to DEP20 develops.…”
Section: Comparison Of the Appetite Suppressantsmentioning
confidence: 99%
“…After 6 months the saliva flow returned to normal. This reduction in salivary flow in patients before surgery and newly operated patients may be associated with the treatment for diabetes in most obese patients 23 . Whereas, the use of medications for hypertension, diabetes, hyperlipidemia and antidepressants decreased significantly after only 3 months of bariatric surgery 23 .…”
Section: Oidpmentioning
confidence: 93%
“…Treatment with amfepramone led to greater loss of body weight than treatment with placebo in all studies (28,30,37,38,41,44) regardless of daily dosage and treatment duration (MD =-1.291 kg (95% CI: -1.548; -1.035), heterogeneity test p=0.000; I 2 : 85.5%). After subgroup analysis of treatment duration (short-term: o180 days and long-term: 4180 days) (37).…”
Section: Direct Meta-analysismentioning
confidence: 92%
“…Our review identified only two studies, of 6 and 12 months of follow up, that reported the outcome of 45% weight loss (28,41). The first identified 66.7% of patients reaching such an outcome with amfepramone treatment compared to 25% in the placebo group.…”
Section: Relevance For Decision Makingmentioning
confidence: 99%